2017
DOI: 10.31557/apjcc.2017.2.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Association of the s1799724 and rs1800629 Polymorphisms of the TNF-α Gene with Susceptibility to Cervical Cancer: a Systematic Review and Meta-Analysis based on 24 Case-Control Studies

Abstract: Objective: Some studies have recently focused on the association between TNF-α polymorphisms and cervical cancer; however, results have been inconsistent. In order to drive a more precise estimation, the present systematic review and meta-analysis is performed to investigate the relationship of the TNF-α rs1800629 and s1799724 polymorphisms with cervical cancer risk. Methods: An electronic search was conducted on PubMed, Web of Science, and Google scholar databases, for papers that describe the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The hOGG1 Ser326Cys and APE1 Asp148Glu polymorphisms showed association with cervical carcinogenesis in Chinese population (Chen et al, 2019). Studies on other inflammatory genes reported the association of polymorphism in TNF-α with risk of cervical cancer (Hamadani et al, 2017). Very recently, Das et al, (2021) evidenced the risk of CC in association with XPC gene polymorphism in Bangladeshi women.…”
Section: Impact Of Polymorphism In Base Excision Repair and Nucleotid...mentioning
confidence: 97%
“…The hOGG1 Ser326Cys and APE1 Asp148Glu polymorphisms showed association with cervical carcinogenesis in Chinese population (Chen et al, 2019). Studies on other inflammatory genes reported the association of polymorphism in TNF-α with risk of cervical cancer (Hamadani et al, 2017). Very recently, Das et al, (2021) evidenced the risk of CC in association with XPC gene polymorphism in Bangladeshi women.…”
Section: Impact Of Polymorphism In Base Excision Repair and Nucleotid...mentioning
confidence: 97%
“…The number of normal expressions of LETMD1 in cervical tissues of healthy people with sclerosis is significantly less than that of CC tumors organization (26). However, this still needs to be verified by studying a large number of clinical specimens or animal models of different processes of cervical cell carcinoma (27)(28)(29). The monoclonal antibody prepared in this study has a high specificity of anti-LETMDI, and the threshold of use is low, so it can be successfully applied to actual clinical research (30).…”
Section: Analysis Of the Activity Of Different Cells In CCmentioning
confidence: 99%
“…As is known to all, cancerous changes in the cervix are induced by the overexpression of E6/E7, which is believed to be caused by the integration of HPV DNA to the chromosome of the host (8-10). Meanwhile, HPV E6/E7 overexpression, by increasing the activity of MMP-2 and MMP-9, can promote the migration of cervical cancer cells (11,12). As such, we aimed to perform the detection of HPV E6/E7 mRNA for patients with cervical lesions, so as to provide a reference for the early diagnosis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%